(untitled) (VETERINARIA, 2021)
The objective of this study is to evaluate the prevalence of symptomatic carriage of salmonella in the ovine species and to identify some risk factors related to breeding practices in the central region of Algeria. 127 samples were collected from 118 sheep belonging to 28 farms (65 diarrheal fecal samples, 55 vaginal swabs and 7 fetal organs). Bacteriological research showed that 10.71% of herds, 2.54% of sheep and 2.36% of samples were positive for Salmonella. Vaginal swabs and fetal organ samples revealed no positive cultures for Salmonella, i.e. (0%), while 33.33% and 1.69% of fecal material of ewes and lambs, respectively, were positive for Salmonella enterica subsp arizonae isolated for the first time in Algeria in the ovine species. Risk factor research was carried out using a univariate analysis with Fisher’s exact test; only one factor was identified, namely the presence of cattle on the farm. Salmonella enterica subsp arizonae can be present in the faeces of healthy carrier or symptomatic sheep of all ages, which can represent an important zoonotic reservoir.